Plasma metabolites as potential markers and targets to prevent and treat urolithiasis: a Mendelian randomization study - Zhu, Wuhui; Li, Huan; Zhang, Ming; Ji, Bing; Liu, Zongtao (Frontiers in Molecular Biosciences, 2024)
Background: Studies of the relationship between urinary system diseases and the human plasma proteome have identified several potential biomarkers. However, no studies have elucidated the causal relationship between plasma proteins and Urolithiasis. Objective: To investigate the potential risk of plasma metabolites for Urolithiasis using a two-sample Mendelian randomization (MR) study. Methods: A total of 1400 metabolites were identified in the most comprehensive genome-wide association study (GWAS) of plasma metabolomics in a European population to date, and we used SNPS for plasma metabolites as instrumental variables. In addition, the European GWAS data for urinary calculi included 482123 case samples and 6223 control samples (ebi-a-GCST90018935) as outcomes. The association between plasma metabolites and Urolithiasis risk was evaluated by inverse variance weighting (IVW), supplemented by sensitivity analysis of MR-Egger and MR-PRESSO tests. Results: For the first time, we found a causal relationship between two plasma metabolites (P < 1.03×10 -4 ) and Urolithiasis (P<0.05). 4-hydroxychlorothalonil, an intermediate product of pesticide hydroxychlorothalonil, could promote the formation of Urolithiasis (OR = 1.12), which was a risk factor for Urolithiasis.1-stearoyl-2-arachidonoyl-GPC, an important component of phospholipid metabolism in human body, can inhibit the formation of Urolithiasis (OR = 0.94). Conclusions: Our results suggest that blood metabolites can be used as blood markers and drug targets for the prevention, diagnosis, and treatment of Urolithiasis, and provide a basis for the government to formulate prevention and treatment policies for urolithiasis.